Estranhas criaturas: Drama in teacher education through a gaze at childhoods (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes the use of Drama in initial teacher education in theater, drawing on childhood sociology, on decolonial epistemologies, and on the concept of corazonar (Arias, 2010). The experience, conducted within a course focused on theatrical practices with children, centered on storytelling and narrativity, using the book Estranhas Criaturas by León and Rubio as a pre-text. Drama is proposed as an ethical and sensitive practice of listening and collective creation, capable of challenging colonial and adult-centered logics and expanding ways of teaching with childhoods.
Keywords: drama; teacher education; childhood; decolonial practices; narrativity